The Clinical Features of FLAIR-Hyperintense Lesions in Anti-MOG Antibody Associated Cerebral Cortical Encephalitis with Seizures: Case Reports and Literature Review - Wang, Yun-feng; Liu, Xue-wu; Lin, Jian-ming; Liang, Ji-ye; Zhao, Xiu-he; Wang, Sheng-jun (Frontiers in Immunology, 2021)
Background: The FLAIR-hyperintense lesions in anti-MOG antibody associated cerebral cortical encephalitis with seizures (FLAMCES) has been recently reported. The clinical features and outcome of this rare clinico-radiographic syndrome remain unclear. Methods: The present study reported two new cases. In addition, cases in the literature were systematically reviewed to investigate the clinical symptoms, MRI abnormalities, treatments and prognosis for this rare clinico-radiographic syndrome. Results: Twenty-one cases were identified for review, of which the mean age of onset of the patients was 26.8 years. The primary clinicopathological features included seizures (100%), headache (71.4%), fever (52.3%) and other cortical symptoms associated with the encephalitis location (61.9%). The common seizure types were focal to bilateral tonic-clonic seizure (28.6%) and unknown onset tonic-clonic seizure (38.1%). The cortical abnormalities in the MRI FLAIR image were commonly located in the frontal (58.8%), parietal (70.6%) and temporal (64.7%) lobes. In addition, pleocytosis in the CSF was reported in the majority of the patients (95.2%). All patients received a treatment regimen of corticosteroids and nine patients used anti-epileptic drugs. Clinical improvements were achieved by all the patients; nevertheless, one third of patients reported relapse following recovery from cortical encephalitis. Conclusions: FLAMCES is a rare phenotype of MOG associated disease. Thus, the recognition of this rare syndrome may promote the timely diagnosis and the development of suitable treatment regimens.